PENGARUH TINGKAT SIMPANAN DAN PINJAMAN ANGGOTA TERHADAP SHU KOPERASI KPRI PKS KOTA SUKABUMI JAWA BARAT - ZAIN LIZSA (LP2M CBI Press, 2016)
This study aims to determine the effect of the level of savings and loans of members partially, simultaneously, and most dominantly on the SHU of the KPRI PKS Cooperative in Sukabumi City.This type of research is descriptive with a quantitative approach where the unit of analysis is the financial statements of the KPRI PKS Cooperative in Sukabumi City and the samples are savings, loans, and cooperative SHU for the fiscal year 2010 to 2014. Data analysis was carried out using simple and multiple regression and correlation methods. Data were collected through documentation, interviews, and literature studies.Based on the results of the study, it is known that partially there is an insignificant effect between member savings and loans on cooperative SHU. Simultaneously there is an insignificant effect between member savings and loans on cooperative SHU, and member savings variables have the most dominant effect on KPRI PKS Cooperative SHU.Based on the results of research and discussion, it is suggested that efforts are needed to improve financial performance and increase income by empowering all business units. Keywords: Member Savings, Member Loans, SHU, and Financial Statements